2012
DOI: 10.1103/physrevlett.109.080502
|View full text |Cite
|
Sign up to set email alerts
|

Coherent Diabatic Ion Transport and Separation in a Multizone Trap Array

Abstract: We investigate the dynamics of single and multiple ions during transport between and separation into spatially distinct locations in a multizone linear Paul trap. A single 9Be+ ion in a ~2 MHz harmonic well was transported 370 μm in 8 μs, corresponding to 16 periods of oscillation, with a gain of 0.1 motional quanta. Similar results were achieved for the transport of two ions. We also separated chains of up to 9 ions from one potential well to two distinct potential wells. With two ions this was accomplished i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
292
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 247 publications
(299 citation statements)
references
References 22 publications
1
292
0
1
Order By: Relevance
“…The QCCD architecture requires exquisite control of the atomic ion positions during shuttling and may require additional atomic ion species to act as 'refrigerator' ions to quench the excess motion from shuttling operations. 34 Rudimentary versions of the QCCD idea have been employed in many quantum information applications such as teleportation and small quantum algorithms, 9 and recent experiments have shown the reliable, repeatable and coherent shuttling of ion qubits over millimetre distances in microsecond timescales 35,36 and through complex 2D junctions. [37][38][39][40] The QCCD approach will help usher the development of trapped ion quantum computers with perhaps 50-1,000 qubits.…”
Section: Ion Trap Qubits and Wiresmentioning
confidence: 99%
“…The QCCD architecture requires exquisite control of the atomic ion positions during shuttling and may require additional atomic ion species to act as 'refrigerator' ions to quench the excess motion from shuttling operations. 34 Rudimentary versions of the QCCD idea have been employed in many quantum information applications such as teleportation and small quantum algorithms, 9 and recent experiments have shown the reliable, repeatable and coherent shuttling of ion qubits over millimetre distances in microsecond timescales 35,36 and through complex 2D junctions. [37][38][39][40] The QCCD approach will help usher the development of trapped ion quantum computers with perhaps 50-1,000 qubits.…”
Section: Ion Trap Qubits and Wiresmentioning
confidence: 99%
“…State initialization, readout, and quantum logic gates have been demonstrated in several systems with small numbers of trapped ions using various atomic species including 9 Be + , 25 Mg + , 40 Ca + , 43 Ca + , 88 Sr + , 111 Cd + , 137 Ba + , and 171 Yb + . The basic elements of scalable QIP have also been demonstrated in multi-zone trap arrays [7,8].…”
mentioning
confidence: 99%
“…For example by using ultrafast lasers, single qubit gate times as fast as 50 ps have been achieved [37] and two-qubit gate times can in principle be considerably improved [38,39]. Transport in the model is limited to 1 m/s but recent experiments have shown that a transport speed of 40-80 m/s can be achieved while still controlling the quantum states of the ion motion [40,41].…”
Section: Discussionmentioning
confidence: 99%